Pharmacological characterization of the seven human NOX isoforms and their inhibitors - Augsburger, Fiona; Filippova, Aleksandra; Rasti, Delphine; Seredenina, Tamara; Lam, Magdalena; Maghzal, Ghassan; Mahiout, Zahia; Jansen-Dürr, Pidder; Knaus, Ulla G.; Doroshow, James; Stocker, Roland; Krause, Karl-Heinz; et al. (Redox biology, 2019)
NADPH oxidases (NOX) are a family of flavoenzymes that catalyze the formation of superoxide anion radical (O ) and/or hydrogen peroxide (H O ). As major oxidant generators, NOX are associated with oxidative damage in numerous diseases and represent promising drug targets for several pathologies. Various small molecule NOX inhibitors are used in the literature, but their pharmacological characterization is often incomplete in terms of potency, specificity and mode of action. We used cell lines expressing high levels of human NOX isoforms (NOX1-5, DUOX1 and 2) to detect NOX-derived O or H O using a variety of specific probes. NOX inhibitory activity of diphenylene iodonium (DPI), apocynin, diapocynin, ebselen, GKT136901 and VAS2870 was tested on NOX isoforms in cellular and membrane assays. Additional assays were used to identify potential off target effects, such as antioxidant activity, interference with assays or acute cytotoxicity. Cells expressing active NOX isoforms formed O , except for DUOX1 and 2, and in all cases activation of NOX isoforms was associated with the detection of extracellular H O . Among all molecules tested, DPI elicited dose-dependent inhibition of all isoforms in all assays, however all other molecules tested displayed interesting pharmacological characteristics, but did not meet criteria for bona fide NOX inhibitors. Our findings indicate that experimental results obtained with widely used NOX inhibitors must be carefully interpreted and highlight the challenge of developing reliable pharmacological inhibitors of these key molecular targets.